Jepun sejarah sebuah negara - Reischauer, Edwin O. (Edwin Oldfather) 1910-1990 (Penerbit Universiti Malaya, 2006)
This text chronicles the evolution of premodern (early A.D. to 1850), modern (1850-1945), and postwar (1945-1989) Japanese civilization from imperial rule through the death of Emperor Hirohito. Professor Reischauer, a former U.S. ambassador to Japan, explores the roots and development of the military dictatorship that brought Japan into World War II, the dubious leadership of its emperor, and the effects of the postwar American occupation.